Dual metal Co-anchored nanosheets to catalyze advanced oxidation processes for highly efficient oxytetracycline degradation. Issue 11 (27th September 2022) - Li, Meng; Yan, Jian-Fang; Zhang, Zhao-Xin; Han, Wei; Zhou, Shao-Qi; Yeung, King Lun; Mo, Ce-Hui
Abstract : Advanced oxidation processes (AOPs) as an efficient oxidation technology, have been extensively applied for degrading recalcitrant organic contaminants via the generated reactive oxygen species from the activation reaction of catalysts. Abstract : Advanced oxidation processes (AOPs) as an efficient oxidation technology, have been extensively applied for degrading recalcitrant organic contaminants via the generated reactive oxygen species from the activation reaction of catalysts. However, the leaching of metal ions and the consumption of catalysts have brought the incomplete degradation of target contaminants, the generation of wastewater containing toxicity, and the increase in costs. Here, dual metal Fe and Co co-doped g-C3 N4 composite (N/CoFeX) was successfully synthesized and used as an efficient peroxymonosulfate (PMS) activator for oxytetracycline (OTC) degradation with a slight leaching of metal ions and superb degradation performance. In addition, the specific insertion structure and the formation of the Fe–O–Co bond into N/CoFeX can bring remarkable catalytic ability and stability, which further prevents the leaching of Co (0.004 mg L −1 ) and Fe ions (0.005 mg L −1 ) and achieves an efficient OTC removal rate (100%) within 60 min. Further calculations show that the lowest adsorption energy of PMS on N/CoFeX aids in PMS activation and can boost the electron transfer from organic pollutants to PMS, further enhancing the generation of radicals and the decomposition of OTC. The relatively slight toxicity of the degradation intermediates examined by proteomics analysis strongly as well as minor leaching of metal ions exhibit great potential for large-scale applications of AOPs in the field of wastewater purification and remediation.